2014
DOI: 10.1155/2014/918346
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Surgical Approaches for Adrenal Tumors: Lateral Transperitoneal versus Posterior Retroperitoneal and Laparoscopic versus Robotic Adrenalectomy

Abstract: Background. Laparoscopic lateral transperitoneal adrenalectomy (LTA) has been the standard method for resecting benign adrenal gland tumors. Recently, however, laparoscopic posterior retroperitoneal adrenalectomy (PRA) has been more popular as an alternative method. This systematic review evaluates current evidence on adrenalectomy techniques, comparing laparoscopic LTA with PRA and laparoscopic adrenalectomy with robotic adrenalectomy. Methods. PubMed, Embase, and ISI Web of Knowledge databases were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 44 publications
8
45
1
Order By: Relevance
“…Patients in both the groups had similar conversion rates and overall complications. 35 The same findings have been corroborated in another meta-analysis and systematic review by Chai et al 36 RA has been compared with conventional LA in a certain subset of patients too. Aksoy et al compared outcomes of these two approaches in obese patients (42 patients in robotic group and 57 in laparoscopic group).…”
mentioning
confidence: 54%
“…Patients in both the groups had similar conversion rates and overall complications. 35 The same findings have been corroborated in another meta-analysis and systematic review by Chai et al 36 RA has been compared with conventional LA in a certain subset of patients too. Aksoy et al compared outcomes of these two approaches in obese patients (42 patients in robotic group and 57 in laparoscopic group).…”
mentioning
confidence: 54%
“…Open transperitoneal adrenalectomy has been the gold standard of treatment for adrenal disease (Chai et al 2014). Other types of adrenal surgery are laparoscopic lateral transperitoneal adrenalectomy (LTA), laparoscopic posterior retroperitoneal adrenalectomy (PRA) and robotic surgery.…”
Section: Surgery Of Pheochromocytomamentioning
confidence: 99%
“…LTA has been the standard method for resecting benign adrenal gland tumors. Recently, however, PRA has been more popular as an alternative method (Chai et al 2014).…”
Section: Surgery Of Pheochromocytomamentioning
confidence: 99%
“…In fact, a more recent literature review has shown that robotic adrenalectomy, when performed at high-volume centers, has superior results to the laparoscopic approach, with lower estimated blood loss, shorter hospital stay, and improvement in intra-operative time with a higher case volume [71]. This is an improvement over a prior meta-analysis published 2 years earlier which had concluded that there is no advantage of robotic adrenalectomy over laparoscopic adrenalectomy [72].…”
Section: Endocrine Surgery: Robotics In Unusual Placesmentioning
confidence: 93%